My dirty story about gardening: a visual autoethnography. (8th August 2016) - Pope, Clive C.
Abstract : Purpose: – The purpose of this paper is to promote visual autoethnography as a tool to explore and represent the captive qualities associated with gardening. Design/methodology/approach: – Visual autoethnography is presented as a method to explore the personal meaning of gardening. Visual autoethnography allows the writer to enmesh narratives of memory, sensual experiences and the self with images that amplify personal meaning. Findings: – The garden is a sensual landscape offering potential for personal expression and the vagaries of the human spirit. Despite its prominence as a leading leisure time activity in Aotearoa New Zealand gardening has received little serious scrutiny. What does this tell us? Is there a need to restore meaning or at least bring meaning to the fore of garden conversations be they personal, agreed, shared, reinforced or not? Originality/value: – While research into gardens and gardening has largely focussed on the other, this paper explores meaning through the self. The meaning of gardening is presented as a highly reflexive endeavor. Images allow the reader to migrate to the ethnographic site and share the ineffable properties that can be associated with what Francis Bacon once described as the purest of human pleasures.